PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MELALUI PENERAPAN MODEL COOPERATIVE LEARNING DENGAN BERTUKAR TEMPAT DI KELAS IV A SDN JENGGAWAH 01 JEMBER SEMESTER GANJIL TAHUN 2012/2013 - Hari - (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2014)
In accordance with the previous background of the study, some research problems can be formulated as follows: (1) How is the implementation of using cooperative learning through the model of student-to-student exchange to enhance the students’ achievement inBahasa Indonesia at the students of class IV A SDN Jenggawah 01 Jember in academic year 2012/2013?; (2) Can and to what extent cooperative learning through the model of student-to-student exchange enhance the students’ achievement inBahasa Indonesia at the students of class IV A SDN Jenggawah 01 Jember in academic year 2012/2013?Whereas, this study carried out to meet the following objectives: (1) To know how the implementation of cooperative learning through the model of student-to-student exchange to enhance the students’ achievement inBahasa Indonesia at the students of class IV A SDN Jenggawah 01 Jember in academic year 2012/2013 is, and (2) to describe whether or not and to what extent the implementation of cooperative learning through the model of student-to-student exchange enhance the students’ achievement inBahasa Indonesia at the students of class IV A SDN Jenggawah 01 Jember in academic year 2012/2013.The research findings show that the students’ achievement of Bahasa Indonesia has significantly increased through the implementation of cooperative learning by the model of studentto-student exchange. So, it perfectly proved that this method can enhance the students’ achievement in Bahasa Indonesia. Keywords: Cooperative learning, model by student-to-student exchange, Students’ achievement, Bahasa Indonesia.